La question du secret professionnel dans l’intervention clinique auprès des délinquants adultes - Lusignan, Richard (Criminologie, 1993)
The conditions and the rules of practice in clinical settings limit the client's right to confidentiality. These limits are reviewed in the case of criminologists : some limits are legal while others refer to the context, the expectations and the reticences shared by the speakers in presence.In regard to past crimes and s elf-incrimination, these questions raise fundamental issues both to the level of ethics and administration of the penal justice. Besides the latter, is there a place for moral justice in our social control system ?